Measuring the short-term economic impacts of ecological restoration: FE1133, 4/2023 - Botta, Robert; Court, Christa D.; Camp, Edward V. (EDIS, 2023)
Increasing demand for ecological restoration has resulted in the development of a “restoration economy” in the United States. Often, the implementation phase of restoration efforts involves substantial capital and labor investments, the short-term economic impacts of which should not be ignored when evaluating the outcomes of restoration efforts. This publication describes the relevant economic impact analysis methods and summarizes a case study application of these methods for the restoration of the Lone Cabbage Reef (LCR) Complex, a recently restored oyster reef in Florida. It should be useful to local governments, outreach and Extension agents, and management agency personnel who want to better understand the economic impacts of restoration actions.